2009
DOI: 10.1021/jp901224n
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles−CdS Quantum Dots/N3 Dye Molecules: Dual Photosensitization

Abstract: We developed dual photosensitization, in which CdS quantum dots serve as a sandwich layer between the ZnO nanoparticles (NPs) and N3 dye molecules, alleviating the serious issues of CdS photocorrosion and the Zn 2+ /N3 dye complex formation leading to insulating surface aggregation. The improvement in the solarto-electrical conversion efficiency from 0.11 and 0.85 to 3.04% when compared to ZnO/N3 and ZnO-CdS, respectively, is attributed to the effective coupling between the ZnO NPs/N3 dye molecules in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…(IV) At time longer than 10 -6 s (P2), the time of TPV maximum of ZnWO 4 /CdS composite in comparison to that of the bare CdS is strongly retarded, which is typical for diffusion photovoltage. These result indicates that ZnWO 4 grown on the surface of CdS can restrict a part of photoinduced hole and inhibit the photocorrosion of CdS [16]。The larger retardation time is, the lower recombination rate of electron-hole pairs will be. This means that photo-induced charges will have more time to participate in the photocatalytic reaction before recombination.…”
Section: Resultsmentioning
confidence: 88%
“…(IV) At time longer than 10 -6 s (P2), the time of TPV maximum of ZnWO 4 /CdS composite in comparison to that of the bare CdS is strongly retarded, which is typical for diffusion photovoltage. These result indicates that ZnWO 4 grown on the surface of CdS can restrict a part of photoinduced hole and inhibit the photocorrosion of CdS [16]。The larger retardation time is, the lower recombination rate of electron-hole pairs will be. This means that photo-induced charges will have more time to participate in the photocatalytic reaction before recombination.…”
Section: Resultsmentioning
confidence: 88%
“…The multi-QD sensitized ZnO or TiO 2 photoelectrodes in PV or PEC devices consist of a film of randomly packed nanoparticles [13,15,16] or orientated arrays [17e19]. Even a type-I band structure between the relative band positions of bulk CdS and CdSe, superior photogenerated carrier collection between CdS and CdSe QDs during PEC operation had been demonstrated due to Fermi level alignment [20].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductors such as CdS [10,11], PbS [12,13], Bi 2 S 3 [14], CdSe [15], and InP [16] which absorb light in the visible region, can serve as sensitizers as they are able to transfer photogenerated electrons to large band gap semiconductors such as TiO 2 or SnO 2 or ZnO. Over the past few years, the assembling of quantum dots with higher absorption coefficient on the polycrystalline surfaces of the ZnO nanostructures has been investigated as an alternative of conventional dye-sensitized solar cell [17,18]. Guerguerian et al reported improved conversion efficiency of solar cells based on ZnO@CdS core-shell nanocrystals [19].…”
Section: Introductionmentioning
confidence: 99%